Perdagangan Sutra Dalam Peradaban Islam Abad ke-16 M: Rivalitas Ekonomi Kesultanan Ottoman dan Dinasti Safawiyah di Timur Tengah - Rifqi Firmansyah (Yayasan Haiah Nusratul Islam, 2026)
The silk trade formed a vital pillar of the Islamic economy and politics during the 16th century, becoming the main arena of economic rivalry between the Ottoman Empire and the Safavid Dynasty. This study explores how Persian silk, primarily produced in Gilan and Shirvan, served as a strategic commodity influencing the financial power and geopolitical position of both empires. Employing historical research methods including heuristic, source criticism, interpretation, and historiography this study analyzes primary and secondary sources. Results show that the Ottomans dominated overland routes via Bursa and Aleppo, gaining substantial tax revenue and using embargoes as weapons. The Safavids under Shah Abbas I responded with a state monopoly on silk, partnership with Armenian merchants, and alternative routes through the Persian Gulf and Russia.The rivalry drove trade innovation while intensifying political-religious tensions, highlighting silk’s crucial role in shaping power dynamics in the Middle East.